Effectiveness Of Manual Direction Test (MDT) With Kinesio Taping Fascia Correction Technique For The Immediate Improvement Of Shoulder Pain Free Range Of Motion In Patients With Rotator Cuff Disease - Vybhav S, Vybhav S; Tiwari, Mukesh; Kumar Saharan, Ajeet; Choudhary, Priya; Yogeshwar, Dharmita; Singh, Janvhi; Saini, Hari Narayan (Journal of Neonatal Surgery, 2025)
Rotator cuff disease, caused by injury or overuse, leads to pain and limited mobility. Common conditions include tears and tendinitis. Kinesio Taping and Manual Direction Test (MDT) can aid healing by improving tissue mobility and reducing pain. The objective of this study was to evaluate the immediate effect of Manual Direction Test with Kinesio-taping fascia correction technique in improving pain-free shoulder range of motion (ROM) in rotator cuff disease patients. An interventional pretest-posttest design was conducted with 40 patients diagnosed with rotator cuff disease and painful shoulder ROM, selected via non-probability convenience sampling from Kerala. Shoulder assessments were performed pre- and post-taping using the Visual Analogue Scale (VAS) for pain and a goniometer for ROM. The result showed that intervention significantly improved the range of motion in both flexion (from M = 103.75 to M = 121.05) and abduction (from M = 97.57 to M = 115.7), with (t(39) = -6.340, p < 0.01). VAS scores also significantly decreased from (M = 7.31 to M = 6.00) with (t(39) = 10.952, p < 0.01). These findings demonstrate the intervention's effectiveness by noticeable progress in mobility, with increased flexibility and movement post-intervention. Additionally, there was a decrease in pain levels. The study concluded that the Kinesio-taping fascia correction technique with MDT, significantly improves Range of Motion and reduces shoulder pain in rotator cuff disease patients.